2020
DOI: 10.30892/gtg.28103-450
|View full text |Cite
|
Sign up to set email alerts
|

Local Residents’ Participation in Tourism at a World Heritage Site and Limitations: A Case of Aksu-Jabagly Natural World Heritage Site, Kazakhstan

Abstract: Ge eo oJ Jo ou ur rn na al l o of f TTo ou ur ri is sm m a an nd d G Ge eo os si it te es s Year X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Similarly, Ladkin and Bertramini (2002) argued that according to tourism stakeholders in Cusco, the current authorities should have controlled the development of tourism, but that there was a general view which stated that the stakeholders' ideas were not taken into consideration. A study conducted in Aksu-Jabagly Natural World Heritage Site in Kazakhstan, Akbar et al (2020) showed that fewer tourists and a lack of preferential policies supporting local residents were the obstacles hindering community participation. Eyassu et al (2019) ranked lack of coordination among stakeholders and poor community involvement among the reasons why the local community did not take advantage of tourism in Shonke Village, Ethiopia, despite the area having great potential in terms of tourism resources.…”
Section: Community Participation In the Decision-making Processmentioning
confidence: 99%
“…Similarly, Ladkin and Bertramini (2002) argued that according to tourism stakeholders in Cusco, the current authorities should have controlled the development of tourism, but that there was a general view which stated that the stakeholders' ideas were not taken into consideration. A study conducted in Aksu-Jabagly Natural World Heritage Site in Kazakhstan, Akbar et al (2020) showed that fewer tourists and a lack of preferential policies supporting local residents were the obstacles hindering community participation. Eyassu et al (2019) ranked lack of coordination among stakeholders and poor community involvement among the reasons why the local community did not take advantage of tourism in Shonke Village, Ethiopia, despite the area having great potential in terms of tourism resources.…”
Section: Community Participation In the Decision-making Processmentioning
confidence: 99%
“…Approximately 150,000 people live in the transition area of the nature reserve (Kazakhstan National Committee, 2014). In the last 10 years, ecological tourism has become highly popular in the reserve, mainly due to tourism for bird watching and plant research and wildlife seeing, and the 59 km area of Tulkibas is located along with the Western Europe-Western China (WE-WC) Highway (Figure 1), it provides convenience for auto travel to this nature reserve (Akbar et al, 2020b).…”
Section: An Overview Of the Study Area: Aksu-jabagly Natural Reservementioning
confidence: 99%
“…The main economic activities are agriculture, plant growing, and cattle breeding. The 59 km area of Tulkibas is located along the Western Europe-Western China (WE-WC) Highway (Figure 1), and it provides convenience to travel to village Zhabagly by car for visitors (AKBAR et al, 2020b).…”
Section: A Brief Overview Of the Study Areamentioning
confidence: 99%
“…Approximately 150,000 people live in the transition area of the SNR. In the last 10 years, ecological tourism has become highly popular in the reserve, mainly due to tourism for bird watching and plant research and wildlife seeing (Akbar et al, 2020a).…”
Section: A Brief Overview Of the Study Areamentioning
confidence: 99%